Strategic Transition From High-Yield to Lifestyle Banking: A Data-Driven Feature Prioritization Framework For Krom Bank (International Journal of Economics and Management Research, 2024)
This research addresses the strategic challenge facing Krom Bank as it transitions from a high-yield savings model to a comprehensive lifestyle banking ecosystem in Indonesia's competitive digital banking landscape. Using a quantitative research design, the study surveyed 281 respondents (100 KROM users and 181 non-KROM users) to identify consumer preferences and prioritize feature development to achieve sustainable competitive advantage. The research framework integrated UTAUT (Unified Theory of Acceptance and Use of Technology) constructs, along with a gap analysis, spider chart analysis, and strategic scoring across 12 dimensions. All measurement constructs demonstrated acceptable-to-good reliability, with the confirming sample adequacy. This research validates Krom Bank’s strategic transition from a high-yield niche to a comprehensive lifestyle ecosystem. The primary solution identifies Transport Payment Integration as the optimal "Daily Anchor" to convert passive savers into active transactors. Concurrently, gap analysis mandates a critical secondary solution: overhauling Customer Service and Security infrastructure to close fundamental trust deficits. Synthesized via the Strategy Diamond framework, the roadmap prioritizes stabilizing trust before anchoring daily habits, ultimately evolving Krom’s economic logic from high-cost deposit dependency to a sustainable, transaction-led model.